2019
DOI: 10.1155/2019/6090965
|View full text |Cite
|
Sign up to set email alerts
|

Development andIn-VitroEvaluation of pH Responsive Polymeric Nano Hydrogel Carrier System for Gastro-Protective Delivery of Naproxen Sodium

Abstract: Current research work was carried out for gastro-protective delivery of naproxen sodium. Polyethylene glycol-g-poly (methacrylic acid) nanogels was developed through free radical polymerization technique. Formulation was characterized for swelling behaviour, entrapment e ciency, Fourier transform infrared (FTIR) spectroscopy, Di erential scanning calorimetry (DSC), and ermal Gravimetric Analysis (TGA), Powder X-ray di raction (PXRD), Zeta size distribution, and Zeta potential measurements, and invitro drug rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Different comonomers give different hydrophobicity to the hydrogels, causing different pHsensitive behaviors. Examples of these are hydrogels based on poly (lactic acid), methoxyl poly (ethylene glycol), and itaconic acid prepared by Ke Wang; pH-responsive co-polymeric hydrogels studied by Umaira Rehman; and polyacrylamide grafted pectin pH-sensitive hydrogel reported by Prashant B. Sutar (Omidia et al, 2019;Sarfraz et al, 2019;Rehman et al, 2021).…”
Section: Ph-sensitive Hydrogelsmentioning
confidence: 99%
“…Different comonomers give different hydrophobicity to the hydrogels, causing different pHsensitive behaviors. Examples of these are hydrogels based on poly (lactic acid), methoxyl poly (ethylene glycol), and itaconic acid prepared by Ke Wang; pH-responsive co-polymeric hydrogels studied by Umaira Rehman; and polyacrylamide grafted pectin pH-sensitive hydrogel reported by Prashant B. Sutar (Omidia et al, 2019;Sarfraz et al, 2019;Rehman et al, 2021).…”
Section: Ph-sensitive Hydrogelsmentioning
confidence: 99%
“…By using the UV/vis spectrophotometer, the drug released was calculated by determining the absorbance at 233 nm. The same procedure was performed for every formulation to study the in vitro drug release [21].…”
Section: In Vitro Drug Release Studiesmentioning
confidence: 99%
“…The method involved grafting methacrylic acid onto PEG-6000 using methylene bis-acrylamide as a cross-linker. PEG-6000 was chosen based on a critical literature survey, and the copolymeric nanogels were characterized using swelling and release studies . The PEG base hydrogel has tunable structural attributes including cross-linked density, which aids in controlled drug diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…PEG-6000, a nontoxic and water-soluble biomaterial, finds various applications in wound healing, drug delivery, and biomedical fields . Earlier research has demonstrated that PEG-6000-based targeted drug delivery systems can effectively deliver peptides and proteins in a controlled manner . The release of drugs from such systems is influenced by the preparation method, molecular weight, and drug solubility .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation